Evaluasi Formulasi Sediaan Floating Mikroenkapsulasi yang Mengandung Ekstrak Etanol Daun Salam (Syzygium Polyanthum) - Rahma Yulina Al-Farini; Razoki Razoki; Muhammad Yunus; Hariyadi Dharmawan Syahputra (Lembaga Pengembangan Kinerja Dosen, 2025)
Ethanol extract of bay leaves is known to have pharmacological activities such as anti-inflammatory, antihypertensive, and antidiabetic. However, its stability and solubility are still challenges. Therefore, a microencapsulation-based delivery system with floating characteristics that can last longer in the stomach was developed. This study aims to evaluate floating microencapsulation preparations containing ethanol extract of bay leaves (Syzygium polyanthum) as an effort to increase the effectiveness and bioavailability of active substances orally. The results showed that microencapsulation had a total floating of more than 4 hours with a water content of 0.47% -2.14%. Stability tests showed no significant changes in physical and chemical characteristics after cycling tests.